Peran Pemerintah dalam Perlindungan Hiu di Indonesia - Aulia, Made Ayu Ananda; Windiani, Reni (Journal of International Relations, 2021)
Shark hunting in Indonesia is increasing, making the government make several efforts to respond to this phenomenon. One of the efforts made by the government is to ratify CITES both in its legal products and policies. This study aims to determine the extent of the government's role in protecting sharks in Indonesia. This study uses a qualitative research method with a descriptive type of using the concept of compliance approach by Robert B. Mitchell. The results of this study found that the government's role in protecting sharks in Indonesia is still not optimal. The government still has not met the targets expected by CITES. Therefore, Indonesia's level of compliance with the IEA is classified as Coincidental Compliance.